Scientific American. – 1865. – Vol. 12, № 1 - б/а (New York. Munn & Company, 1865)
A weekly journal of practical information in art, science, mechanics, chemistry and manufactures.
Scientific American. Vol. 12, № 1, 3–26. – New York, 1865. – P. 1–14, 31–414.
Keywords: Research Subject Categories::TECHNOLOGY; Research Subject Categories::TECHNOLOGY::Engineering physics; Research Subject Categories::NATURAL SCIENCES::Chemistry; Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::History subjects::History of science and ideas; Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::History subjects::Technology and culture; Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::History subjects::History of science; January 2, 1865; Jacob's system of wheel manufacture; wheel manufacturing machine; seasoning of lumber and timber; Bulkley H.G.; Water Engines in Europe; The Patent Stone Bricks; Recent American Patents; manufacture of Aluminum; Shelley’s Axle Box; Improved Axle Box; professor Rankine on expansion; oil stock excitement; professor Doremus’s lectures; Letters Patent; musical magazine of America; the musical host; Brinkerhoff A.W.; Brinkerhoff’s Ohio corn husker; Porter's sifter shovel